Faktor-Faktor Yang Berpengaruh Terhadap Pertumbuhan Ekonomi Di Luwu Raya - Aqila, Nila; Patra, I Ketut; Maming, Rian (Efektor, 2023)
Abstract This research aims to identify the factors that influence the economy in Luwu Raya. In this study, government expenditure and labor are considered as independent variables, while economic growth is considered as the dependent variable. The basic theories used in this research include Keynesian theory (Harrod-Domar) and John Stuart Mill's theory, which explain how government policies and labor relations affect economic growth. Data on government expenditure by expenditure type disclosed by BPS Luwu Raya and GDP data based on constant prices in 2010 with annual data from 2012 to 2021 for the business sector are the information used in this research. Labor data for Luwu Raya is annual information covering the years 2012 to 2021. The SPSS version 20 application is used for multiple regression-based analysis. The results of the research show that government expenditure has a significant and positive impact on the economic growth of Luwu Raya, while labor does not have a significant influence on economic growth. In this study, the independent variables contribute to a decrease in the dependent variable, with a value of 0.996 or 99.6%, and 4% of the independent variables are influenced by other variables during the study. Therefore, it can be concluded that government expenditure is an important factor that influences economic growth in Luwu Raya.